Furosemide cocrystals with pyridines: an interesting case of color cocrystal polymorphism - Sangtani, Ekta; Sahu, Sanjay Kumar; Thorat, Shridhar H.; Gawade, Rupesh L.; Jha, Kunal K.; Munshi, Parthapratim; Gonnade, Rajesh G. (Crystal Growth & Design, 2015)
Furosemide (FS), a loop diuretic drug commonly used for the treatment of hypertension and edema, exhibited color cocrystal polymorphism with coformer 4,4'-bipyridine (4BPY) in the stoichiometry 2:1, albeit both the API and the cocrystal former are colorless. Crystallization from ethanol, isopropanol, ethanol-water (v/v, 1/1) mixture, and acetonitrile yielded pale yellow (form II, thin needles) and orange (form 1II, blocks) cocrystals concomitantly. Needles appeared from solution within a day, while the blocks were obtained after 1-2 days from the same flask, indicating that yellow needles were formed faster and the orange blocks were perhaps formed under thermodynamic conditions. Form 1I cocrystals could also be produced from the variety of common solvents. Cocrystallization of FS with 2,2'-bipyridine (2BPY) and 4-aminopyridine (4AP) gave colorless cocrystals 2 and 3, respectively, and did not exhibit polymorphism. The single-crystal X-ray structures, powder X-ray diffraction, photophysical characterization, differential scanning calorimetry, hot stage microscopy studies, and density functional theory (DFT) calculations provide insight into the structure property relationship. The common structural features observed in all of the structures is the formation of sandwich motifs comprising FS and pyridines through pi-stacking interactions. These motifs are linked differently through hydrogen bonding interactions in all three directions. The significant color difference between the two cocrystals dimorphs could be attributed to the different pi-stacking patterns and hydrogen bonding interactions between molecules of FS and 4BPY in their cocrystal structures. Investigation on the origin of the color difference using DFT calculations revealed the decrease in HOMO-LUMO gap for form 1II cocrystals (orange) compared to form 1I crystals (light yellow). The crystal-to-crystal thermal transformation of form 1I crystals to form 1II crystals of 1 suggests the role of pi-stacking assemblies in driving the self-assembly.